PENYULUHAN KAIN FLANEL VISUAL BENTUK BINATANG PADA MASKER MEDIS BAGI TAMAN BELAJAR KITA - Widyastuti, Putri Anggraeni; Yusuff, Adisti Ananda; Huddiansyah, Huddiansyah (Jurnal Pengabdian Masyarakat AbdiMas, 2021)
This community service activity was motivated by Taman Belajar Kita, a course that became a solution for parents to distance education during the pandemic era. However, it turns out that Taman Belajar Kita does not wear a mask during teaching and learning activities. For this reason, community service activities were carried out with the aim that Taman Belajar Kita students could wear masks through animal-shaped flannel cloth counseling for Taman Belajar Kita, as a form of learning for them. The scope of community service for this community partnership program is carried out in Taman Belajar Kita, West Jakarta involving PAUD and Kindergarten age students. The implementation method is carried out by identifying stakeholders, collecting and analyzing needs, determining problem solutions, preparation, and implementation (which is also accompanied by assistance) for community service activities at Taman Belajar Kita. The results of community service activities can be seen from the enthusiasm of the students and teachers of Taman Belajar Kita wearing medical masks that are given through a creativity package containing medical masks, explanations for use, and animal-shaped flannel. In conclusion, this community service activity at Taman Belajar Kita can be carried out well through a learning and playing approach while providing a creativity package and also socializing the implementation of the correct process so that the objectives of this activity are well conveyed. Keywords : flannel fabric, medical masks, counseling